(untitled) (Global Journal of Science Frontier Research, 2012)
The purpose of this study was to investigate the effect of technical efficiency on rural poverty between female and male-headed farm families in southwestern part of Nigeria. The study also determined the policy variables that influenced technical efficiency of the poor rural female and male-headed households in the study area using the stochastic frontier methodology. Results of data analysis showed that poor male-headed households were more technically efficient than their poor female-headed households’ counterparts (with mean technical efficiency estimates of about 91% and 82% respectively). Policy measures to reduce level of poverty and to improve efficiency which will lead to higher income were then suggested